In silico screening of microbial metabolites reveals Moromycin B as a potential pancreatic lipase inhibitor - Sayyid, Fatima; Ahmad Nadzirin, Izzuddin; Abdul Hamid, Azzmer Azzar; Alias, Norsyuhada (Institute for Medical Research (IMR), National Institutes of Health (NIH), Malaysia, 2025)
INTRODUCTION: Obesity is a chronic, multifactorial disease contributing to health burdens worldwide. An established therapeutic strategy involves inhibiting pancreatic lipase, the enzyme responsible for dietary fat breakdown in the digestive system. Inhibiting this enzyme prevents fat absorption and promotes excretion, which leads to weight loss. Currently, orlistat is the only FDA-approved pancreatic lipase inhibitor, but its gastrointestinal side effects call for safer alternatives, particularly from natural resources. Microbial metabolites, known for their structural diversity and bioactivity, offer promising potential. This study leverages in silico screening to discover novel microbial metabolites capable of inhibiting pancreatic lipase. OBJECTIVE(S): To identify microbial metabolites that inhibit pancreatic lipase through in silico screening, and to evaluate their interactions with the enzyme’s key catalytic residues, Ser152, His263, and Asp176. MATERIALS & METHODS: The structure of human pancreatic lipase (PDB ID: 1LPB) was retrieved from the Protein Data Bank, and 36,454 microbial metabolites were sourced from Natural Product Atlas. Drug-likeness was filtered using Lipinski’s Rule of Five. Molecular docking was conducted using AutoDock Vina, with orlistat as a reference. Top hits were analysed using the Protein-Ligand Interaction Profiler (PLIP) and visualised in PyMol. RESULTS: Out of 36,454 metabolites screened, 27,297 passed Lipinski’s filter. Among them, moromycin B, which is derived from Streptomyces, exhibited the highest binding affinity (-13.2 kcal/ mol), surpassing that of orlistat (-6.7 kcal/mol). Moromycin B formed a hydrogen bond with the catalytic residue Ser152, suggesting favourable and potentially stable interactions within the enzyme’s active site. CONCLUSION: This in silico study identified moromycin B as a promising microbial inhibitor of pancreatic lipase. While previously recognised for its anticancer properties, its strong binding affinity and favourable interaction with a key catalytic residue in this study suggest a novel therapeutic application as an anti-obesity agent.